2005
DOI: 10.1191/0269215505cr869oa
|View full text |Cite
|
Sign up to set email alerts
|

The reliability of hip scoring systems for total hip arthroplasty candidates: assessment by physical therapists

Abstract: There was an excellent interobserver reliability for all hip scores between the physical therapists, suggesting that all these hip scores are suitable for use by physical therapists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 14 publications
2
37
0
Order By: Relevance
“…Additionally, the Merle d'Aubigné-Postel score, the anterior impingement test, and ROM were assessed by different observers throughout the preoperative and followup visits. Nevertheless, substantial inter-and intraobserver agreement has been reported for these parameters [15,19,24,25,50]; therefore, we believe this does not jeopardize our conclusions in any substantial way. Next, the limited number of 97 hips included in the study series revealed three multivariate predictive factors only (Table 5).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Additionally, the Merle d'Aubigné-Postel score, the anterior impingement test, and ROM were assessed by different observers throughout the preoperative and followup visits. Nevertheless, substantial inter-and intraobserver agreement has been reported for these parameters [15,19,24,25,50]; therefore, we believe this does not jeopardize our conclusions in any substantial way. Next, the limited number of 97 hips included in the study series revealed three multivariate predictive factors only (Table 5).…”
Section: Discussionmentioning
confidence: 68%
“…As a clinical scoring system, the Merle d'Aubigné-Postel [26] score was used. Substantial inter-and intraobserver agreement has been reported for the anterior impingement test [24], ROM [15,25,50], and the Merle d'Aubigné-Postel score [19]. At followup, additional hip scores were assessed including the WOMAC [4], the Harris hip score (HHS) [14], the SF-12 Physical and Mental Component Scales [12,48], and the University of California Los Angeles (UCLA) activity score [51].…”
Section: Methodsmentioning
confidence: 99%
“…This is an unavoidable potential source of error for a retrospective study spanning more than a decade. Nevertheless, because the assessed clinical parameters could be proven to have substantial interobserver and intraobserver agreement [13,16], we do not believe this would jeopardize our observations or conclusions. Third, the radiographs in the first series were not taken in a standardized manner.…”
Section: Discussionmentioning
confidence: 72%
“…Substantial inter-and intraobserver agreement has been reported for ROM [6,13] and the Merle d'Aubigné-Postel scoring system [10].…”
Section: Methodsmentioning
confidence: 96%